The level-1 trigger for the SuperCDMS experiment at SNOLAB. (1st July 2022) - Wilson, J.S.; Meyer zu Theenhausen, H.; von Krosigk, B.; Azadbakht, E.; Bunker, R.; Hall, J.; Hansen, S.; Hines, B.; Loer, B.; Olsen, J.T.; Oser, S.M.; Partridge, R.; et al.
Abstract: The SuperCDMS SNOLAB dark matter search experiment aims to be sensitive to energy depositions down to 𝒪(1 eV). This imposes requirements on the resolution, signal efficiency, and noise rejection of the trigger system. To accomplish this, the SuperCDMS level-1 trigger system is implemented in an FPGA on a custom PCB. A time-domain optimal filter algorithm realized as a finite impulse response filter provides a baseline resolution of 0.38 times the standard deviation of the noise, σn, and a 99.9% trigger efficiency for signal amplitudes of 1.1 σn in typical noise conditions. Embedded in a modular architecture, flexible trigger logic enables reliable triggering and vetoing in a dead-time-free manner for a variety of purposes and run conditions. The trigger architecture and performance are detailed in this article.